2003
DOI: 10.1093/jurban/jtg073
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use and Incarceration Adversely Affect HIV-1 RNA Suppression Among Injection Drug Users Starting Antiretroviral Therapy

Abstract: We conducted this study among HIV-infected injection drug users to determine the effect of self-reported alcohol use and prior incarceration at the time of ini

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 40 publications
2
57
0
2
Order By: Relevance
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…Entre esses obstáculos, o uso de álcool, que é um comportamento modificável, temse mostrado como um forte preditor de falhas na adesão e piora no desfecho clínico [25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Discussionunclassified
“…[1][2][3][4][5] These results can be observed even in "difficult" HIV-infected populations (injection drug users, homeless people, ethnic minorities, and others) [6][7][8][9][10] and in "difficult" contexts such as developing countries. 11,12 Providing access to ART for those in need in the context of correctional facilities is a challenge, but it can be feasible following the existing national and/ or international guidelines for HIV/AIDS care and ART use.…”
Section: Defining the Settingmentioning
confidence: 99%
“…28 It is also known that although HIV+ inmates may achieve viral suppression in prison, these advances may be attenuated once they are released to the community. 10 A number of studies and recommendations have highlighted the importance of the link between HIV specialists and correctional health care providers for ensuring that HIV+ patients have optimal care both inside prison and after release. 21,25,27,29 In terms of the prescription of ART in prisons, one study found that 72% of those eligible for treatment in the San Francisco jail were actually receiving therapy and that 71% followed medical advice and picked up medication at release.…”
Section: Continuity Of Carementioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have found that active drug users had sub-optimal adherence, resulting in poorer virologic and immunologic outcomes to HAART compared to former and non-drug users (Lucas et al 2001(Lucas et al , 2002Palepu et al 2003a, b). However, other studies have found that HIVpositive drug users who have access to drug abuse and mental health treatment (Malta et al 2008), and particularly former drug users who are abstinent, can attain the same levels of adherence found among PLWHA who have never used illicit drugs (Crystal et al 2001) and can thus achieve similar survival rates compared to non-drug using populations (Wood et al 2008).…”
Section: Introductionmentioning
confidence: 99%